Pressure effect on the structural properties of amorphous Ag during isothermal annealing - Celik, F. A.; Kazanc, S.; Yidiz, A. K.; Ozgen, S. (Elsevier Sci Ltd, 2008)
In this study, using molecular dynamics (MD) simulations we investigate the effect of pressure on the transformation from amorphous structure to crystalline structure during isothermal annealing of silver (Ag) model system with 2048 atoms. The structural development and phase transformation are analysed based on the variations of the radial distribution function, the bond-orientational order parameters and atomic configurations. In particular, in order to distinguish the local structures and number of clusters in the system the local structure of the system has been analysed from the bond-orientational order parameters. The crystal nucleation in amorphous phase, the growth of crystal nucleus and the formation of stable crystal phase during the crystallization process are also investigated for the model system. The simulation results showed that the applied pressure on the system caused further transformation from amorphous state to stable crystal phase during the crystallization process and also transformations from HCP/DHCP-like to FCC-like local structures. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: molecular dynamics; embedded atom method; solidification; local order; nucleation